High-entropy ceramic oxygen adsorbent material and preparation method thereof
By using the structural formula RBaCo2.5Al0.5Fe0.5Ni0.5O7 of high-entropy ceramic oxygen adsorbent material, combined with the sintering process of hydrothermal method and mixed alkali method, nanopowders with low operating temperature and fast oxygen adsorption and desorption rates were prepared. The bulk high-entropy ceramic oxygen adsorbent material solves the problem of operating existing ceramic oxygen adsorbent materials under high temperature conditions and achieves efficient oxygen adsorption and release.
Patent Information
- Application Number
- CN202411538364.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing ceramic oxygen adsorbent materials can effectively absorb and release oxygen under high temperature conditions, resulting in increased energy consumption and damage to the material structure. At the same time, the oxygen release rate is slow, reducing oxygen production.
The structural formula of the high-entropy ceramic oxygen adsorbent material is RBaCo2.5Al0.5Fe0.5Ni0.5O7. Through a sintering process combining hydrothermal method and mixed alkali method, a low working temperature, low energy consumption, rapid oxygen adsorption and desorption are prepared. Nanopowel high-entropy ceramic oxygen adsorbent material with rate and good cycle stability.
It realizes the high-efficiency oxygen adsorption and release activity at lower temperatures, reduces the oxygen adsorption temperature, increases the adsorption amount, and solves the problems of existing oxygen adsorbent materials operating at high temperatures and producing low oxygen.
Smart Images

Figure CN119409495A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, and in particular to a high entropy ceramic oxygen adsorbent material and a preparation method thereof. Background Art
[0002] Currently, the main materials used as oxygen adsorption media are Ba 0.95 Ca 0.05 Co 0.8 Fe 0.2 O 3-δ ,La 0.2 Sr 0.8 Co 0.8 Fe 0.2 O 3-δ 、SrFeCo 0.5 O 3-δ And RBaCo4O7, etc. Although these materials have excellent oxygen adsorption and release properties, they can only effectively adsorb and release oxygen under high temperature conditions (about 800 to 1000°C). High-temperature operation not only leads to increased energy consumption, but also causes damage to the material structure, which affects the application of oxygen separation materials. At present, when using ceramic-based oxygen adsorbents to separate gas mixtures, there are two major problems: first, the required operating temperature is high, resulting in increased energy consumption; second, the oxygen release rate is slow, which reduces the oxygen production. From this point of view, the development of a ceramic oxygen adsorbent material with large-capacity oxygen adsorption, fast adsorption and release rate, suitable low-temperature operating conditions and good cycle stability will greatly promote the separation of mixed gases. Therefore, finding new materials that can exhibit high-efficiency oxygen adsorption and release activity at lower temperatures has become a key factor in promoting the development of oxygen separation materials.
[0003] In recent years, high entropy alloys have aroused extensive research enthusiasm due to their excellent mechanical and physical properties, unique architecture and broad development prospects. Research on this type of high entropy materials has made important progress, not only limited to traditional high entropy alloy systems, but also expanded to the field of high entropy inorganic non-metallic substances, such as metal carbides, diborides and oxides. When the concept of high entropy is applied to ceramic materials, some unexpected effects are usually produced. As an emerging material, high entropy ceramics have been developed in recent years. It is composed of a variety of different elements, characterized by the fact that the content of these elements is close and evenly distributed in the crystal structure. Compared with traditional ceramic materials, high entropy ceramics are not only more diverse in chemical composition, but also more complex in crystal structure, so they show better mechanical properties, thermal properties, conductivity and thermal stability. However, there are still many challenges in the preparation of such materials. At present, the research on high entropy oxides mainly focuses on rock salt structures, while research on high entropy ceramic oxygen adsorbent materials114 is rarely seen.
[0004] The basic principle behind the design of high-entropy ceramics is to introduce local atomic disorder, where multiple elements occupy equivalent lattice sites. Different elements show changes in valence, ionic radius, electronic configuration and electronegativity, leading to different properties, such as phase stability, atomic disorder with lattice distortion and slow diffusion of elements. High-entropy ceramics have four effects different from conventional ceramics: high entropy effect in thermodynamics, lattice distortion effect in structure, hysteresis diffusion effect in kinetics, and "cocktail" effect in performance. It shows unique structure and high entropy effect and has received widespread attention.
[0005] In the preparation process of high-entropy ceramics, sintering temperature, sintering time and other processes are undoubtedly the most important and core links. The sintering process determines the transformation of the raw material powder particles into high-entropy single-phase functional ceramics through diffusion and mass transfer and mutual reaction. The solid-phase sintering method is the simplest and most commonly used method for preparing ceramics. Traditional sintering technology has problems such as long sintering time, high sintering temperature and coarse grains of sintered samples, which hinder the application and research of high-entropy ceramic materials. However, in order to obtain single-phase functional ceramics, due to the hysteresis diffusion effect and impurity influence of high-entropy materials, it is often necessary to keep warm at high temperature for a long time, which can easily lead to grain coarsening. For example, Patent Publication No. CN104857911A discloses a high-performance oxygen adsorbent and its preparation method, with the structural formula A 1-x A′ x B 1-y B′ y O 3-δ ; Wherein, the value range of x is 0≤x≤0.3, the value range of y is 0≤y≤0.3, 0<δ<0.5; A is at least one or more of the rare earth metal La series, alkaline earth metal Mg, Ca, Sr, Ba; B is at least one or more of the transition metal Co, Al, Fe, Nb, Cu, Zr, Mn, Cr, Ti. The preparation method is: according to the chemical molecular formula of the target oxygen adsorbent, the raw materials are accurately weighed according to the molar ratio of the metal elements, and then ball milled and mixed evenly, and then roasted multiple times at high temperature to prepare a perovskite-type oxide powder with larger particles, and then ball milled again to obtain a multi-metal composite oxide powder, which is the oxygen adsorbent. The roasting temperature of the patent is as high as 900℃-1400℃, and the weight change of the prepared cation adsorbent is only 2.6% when the temperature is increased and decreased between 300-925℃. Therefore, developing new sintering technology, shortening the sintering time, lowering the sintering temperature and obtaining sintered samples with fine grains, lowering the oxygen adsorption temperature and increasing the adsorption amount have become the development goals of high entropy ceramic preparation technology. Summary of the invention
[0006] In view of the technical problems of high sintering temperature and working temperature and low adsorption capacity in the preparation of oxygen adsorption medium, the present invention proposes a high entropy ceramic oxygen adsorbent material and a preparation method thereof. 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 oxygen adsorbent material has the advantages of low operating temperature and low energy consumption; at the same time, the oxygen desorption rate is relatively fast and the oxygen production efficiency is high.
[0007] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] A high entropy ceramic oxygen adsorbent material, the structural formula of the high entropy ceramic oxygen adsorbent material is: RBaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7, R-site elements are at least five of Yb, La, Pr, Sm, Ce and Gd.
[0009] The structural formula of the high entropy ceramic oxygen adsorbent material is: Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0. 5Ni 0.5 O7, high entropy ceramic oxygen adsorbent material has the shape of spherical powder, and the size of the powder is 50-500nm.
[0010] The structural formula of the high entropy ceramic oxygen adsorbent material is: Yb 1 / 6 La 1 / 6 Pr 1 / 6 Sm 1 / 6 Ce 1 / 6 G 1 / 6BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7.
[0011] A method for preparing a high entropy ceramic oxygen adsorbent material, comprising the following steps:
[0012] (1) According to the structural formula of the high entropy ceramic oxygen adsorbent material, metal oxides of R-position elements, BaCO3, Al2O3, Fe2O3 and NiO are weighed according to the stoichiometric ratio;
[0013] (2) dispersing and dissolving the powder, alkaline reagent and morphology control agent weighed in step (1) into a solvent, and then performing a hydrothermal reaction. After the reaction is completed, washing and drying are performed to obtain a porous high-entropy ceramic oxygen adsorbent material;
[0014] (3) The high entropy ceramic oxygen adsorbent material and the chloride salt are mixed and ball-milled, and then the mixed powder is calcined to obtain the high entropy ceramic oxygen adsorbent material.
[0015] The metal oxide of the R-position element is Yb2O3, La2O3, Pr6O 11 , Sm2O3, Ce2O3 or Gd2O3.
[0016] In the step (2), the mass ratio of the powder, the alkaline reagent, the morphology regulator and the solvent is 1:(1-1.5):(1-1.5):(0.6-0.8), wherein the alkaline reagent provides an alkaline environment, such as sodium hydroxide; and the morphology regulator controls the morphology of the powder, such as sodium citrate, sodium bicarbonate or polyvinyl alcohol.
[0017] The solvent includes alcohol and water in a mass ratio of 1: (1-1.5).
[0018] The temperature of the hydrothermal reaction is 150-185° C. and the time is 5-15 hours.
[0019] The mass ratio of the high entropy ceramic oxygen adsorbent material to the chloride salt is 1:(5-10).
[0020] The chloride salt includes NaCl and KCl, and the mass ratio of NaCl to KCl is (40-55): (60-45). The chloride salt is melted at a specific temperature to provide a liquid environment, temperature and pressure environment for the preparation of the powder.
[0021] The calcination temperature is 700-850°C and the calcination time is 8-10h.
[0022] Beneficial effects of the present invention: The present invention utilizes the concept of high entropy ceramics by adding oxygen adsorption material RbaCoO 7+δ The number of elements at the R and Co positions in the structure is used to construct a high entropy structure. A high-pressure and low-temperature sintering process is designed by combining the hydrothermal method with the molten salt method. A product with low sintering temperature, simple method, controllable grain size (50nm-500nm), large specific surface area (up to 30.07-85.05m 2 ·g -1), high entropy ceramic oxygen adsorbent material. The prepared nano high entropy ceramic oxygen adsorbent material has a 114 structure, uniform size distribution, spherical shape, and an outer size of 50-500nm. The lattice constant of the high entropy ceramic oxygen adsorbent material can be adjusted by adjusting the ratio of Yb, La, Pr, Sm, Ce and Gd, so that the synthesized nano high entropy ceramic oxygen adsorbent material has good oxygen adsorption performance and low working temperature, and has the advantages of fast oxygen adsorption / desorption rate and high cycle stability. The mass change of the prepared high entropy ceramic oxygen adsorbent material after oxygen adsorption at 370°C reached 3.17%, and the mass change after oxygen adsorption at 830°C reached 6.49%, which solved the problems of high working temperature, high energy consumption, and slow oxygen adsorption and desorption rate in actual use of existing oxygen adsorbent materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 SEM image of O7 nanopowder high entropy ceramic oxygen adsorbent material.
[0025] Figure 2 Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 Adsorption-desorption curves of O7 nanopowder high entropy ceramic oxygen adsorbent material.
[0026] Figure 3 Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe0.5 Ni 0.5 XRD pattern of O7 nanopowder high entropy ceramic oxygen adsorbent material.
[0027] Figure 4 Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 Oxygen adsorption performance test chart of O7 nanopowder high entropy ceramic oxygen adsorbent material. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] A high entropy ceramic oxygen adsorbent material, structural formula Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0. 5O7, the preparation method thereof comprises the following steps:
[0031] (1) Preliminary treatment of oxygen adsorbent materials using hydrothermal method: Yb2O3, La2O3, Pr6O3 were weighed according to the stoichiometric ratio. 11 , Sm2O3, Ce2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, where the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1:1:0.6, and the ratio of alcohol to water is 1:1. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 15h, the drying temperature is 50℃, and the drying time is 5h.
[0032] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: the high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 40:60, and the above two powders were mixed in a mass ratio of 1:5; then the mixed powder after roller milling was placed in an alumina crucible, kept at 850°C for 8 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 75°C to finally obtain Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0033] Example 2
[0034] A high entropy ceramic oxygen adsorbent material, structural formula Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0. 5O7, the preparation method thereof comprises the following steps:
[0035] (1) Preliminary treatment of oxygen adsorbent materials using hydrothermal method: Yb2O3, La2O3, Pr6O3 were weighed according to the stoichiometric ratio. 11 , Sm2O3, Ce2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, where the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1.5:1.5:0.8, and the ratio of alcohol to water is 1:1.5. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 185℃, the reaction time is 5h, the drying temperature is 60℃, and the drying time is 2h.
[0036] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: The high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 55:45, and the above two powders were mixed in a mass ratio of 1:10; then the mixed powder after roller milling was placed in an alumina crucible, kept at 700°C for 10 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 80°C to finally obtain Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0037] Example 3
[0038] A high entropy ceramic oxygen adsorbent material, structural formula Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0. 5O7, the preparation method thereof comprises the following steps:
[0039] (1) Preliminary treatment of oxygen adsorbent materials using hydrothermal method: Yb2O3, La2O3, Pr6O3 were weighed according to the stoichiometric ratio. 11 , Sm2O3, Ce2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, where the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1.2:1.3:0.7, and the ratio of alcohol to water is 1:1.3. After the reaction is completed, take out the sample, then wash and dry it with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 160℃, the reaction time is 8h, the drying temperature is 55℃, and the drying time is 4h.
[0040] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: The high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 50:50, and the above two powders were mixed in a mass ratio of 1:6; then the mixed powder after roller grinding was placed in an alumina crucible, kept at 790°C for 9 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 78°C to finally obtain Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0041] Example 4
[0042] A high entropy ceramic oxygen adsorbent material, structural formula Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0. 5O7, the preparation method thereof comprises the following steps:
[0043] (1) Preliminary treatment of oxygen adsorbent materials using hydrothermal method: Yb2O3, La2O3, Pr6O3 were weighed according to the stoichiometric ratio. 11 , Sm2O3, Ce2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, where the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1.4:1.4:0.7, and the ratio of alcohol to water is 1:1.4. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 170℃, the reaction time is 11h, the drying temperature is 58℃, and the drying time is 4h.
[0044] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: The high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 55:45, and the above two powders were mixed in a mass ratio of 1:8; then the mixed powder after roller milling was placed in an alumina crucible, kept at 830°C for 9.2 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 79°C to finally obtain Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0045] Figure 1 Preparation of Yb for Example 1 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 SEM image of O7 nanopowder high entropy ceramic oxygen adsorbent material. The powder size is between 50-500nm.
[0046] Figure 2 For the preparation of Yb in Example 1 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 The adsorption-desorption curve of O7 nanopowder high entropy ceramic oxygen adsorbent material is calculated to have a specific surface area of 85.05m 2 ·g -1 .
[0047] Figure 3 Yb prepared in Examples 1, 2, and 3 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5XRD diagram of O7 nanopowder high entropy ceramic oxygen adsorbent material. The test results show that the prepared Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 The O7 nanopowder high entropy ceramic oxygen adsorbent material is highly consistent with the hexagonal close-packed structure represented by the P63mc (186) space group. The XRD pattern of the high entropy ceramic oxygen adsorbent material was accurately marked according to the crystal plane index of this space group, verifying that the high entropy ceramic oxygen adsorbent material has a single 114 structural feature.
[0048] Figure 4 Yb prepared in Examples 1 and 2 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 Oxygen adsorption performance test diagram of O7 nanopowder high entropy ceramic oxygen adsorbent material. In the oxygen adsorption and desorption experiment, about 30 mg of sample powder was placed in an alumina crucible, and the weight change curve of the sample with increasing temperature in an oxygen atmosphere was measured. The test results show that: Yb prepared in Example 1 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 The mass change of O7 nano-powder high entropy ceramic oxygen adsorbent material after absorbing oxygen at 370°C reached 3.17%, and the mass change after absorbing oxygen at 830°C reached 6.49%. 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 The mass change of O7 nano-powder high entropy ceramic oxygen adsorbent material after absorbing oxygen at 370°C reached 2.71%, and the mass change after absorbing oxygen at 830°C reached 5.72%.
[0049] Example 5
[0050] A high entropy ceramic oxygen adsorbent material, structural formula Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 G 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0. 5O7, the preparation method thereof comprises the following steps:
[0051] (1) Preliminary treatment of oxygen adsorbent materials using hydrothermal method: Yb2O3, La2O3, Pr6O3 were weighed according to the stoichiometric ratio. 11 , Sm2O3, Gd2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, where the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1:1:0.6, and the ratio of alcohol to water is 1:1. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 15h, the drying temperature is 50℃, and the drying time is 5h.
[0052] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: the high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 40:60, and the above two powders were mixed in a mass ratio of 1:5; then the mixed powder after roller milling was placed in an alumina crucible, kept at 850°C for 8 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 75°C to finally obtain Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 G 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0053] Example 6
[0054] A high entropy ceramic oxygen adsorbent material, structural formula Yb 0.2 La 0.2 Pr 0.2 Ce 0.2 G 0.2 BaCo 2.5 Al 0.5Fe 0.5 Ni 0. 5O7, the preparation method thereof comprises the following steps:
[0055] (1) Preliminary treatment of oxygen adsorbent materials by hydrothermal method: Yb2O3, La2O3, Pr6O 11 , Ce2O3, Gd2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, where the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1:1:0.6, and the ratio of alcohol to water is 1:1. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 15h, the drying temperature is 50℃, and the drying time is 5h.
[0056] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: the high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 40:60, and the above two powders were mixed in a mass ratio of 1:5; then the mixed powder after roller milling was placed in an alumina crucible, kept at 850°C for 8 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 75°C to finally obtain Yb 0.2 La 0.2 Pr 0.2 Ce 0.2 G 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0057] Example 7
[0058] A high entropy ceramic oxygen adsorbent material, structural formula Yb 0.2 La 0.2 Sm 0.2 Ce 0.2 G 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0. 5O7, the preparation method thereof comprises the following steps:
[0059] (1) Preliminary treatment of oxygen adsorbent materials by hydrothermal method: weigh Yb2O3, La2O3, Sm2O3, Ce2O3, Gd2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials according to the stoichiometric ratio, weigh sodium hydroxide, sodium bicarbonate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, wherein the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1:1:0.6, and the ratio of alcohol to water is 1:1. After the reaction is completed, take out the sample, and then wash and dry the sample with deionized water and alcohol to preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 15h, the drying temperature is 50℃, and the drying time is 5h.
[0060] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: the high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 40:60, and the above two powders were mixed in a mass ratio of 1:5; then the mixed powder after roller milling was placed in an alumina crucible, kept at 850°C for 8 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 75°C to finally obtain Yb 0.2 La 0.2 Sm 0.2 Ce 0.2 G 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0061] Example 8
[0062] A high entropy ceramic oxygen adsorbent material, structural formula Yb 0.2 Pr 0.2 Sm 0.2 Ce 0.2 G 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0. 5O7, the preparation method thereof comprises the following steps:
[0063] (1) Preliminary treatment of oxygen adsorbent materials by hydrothermal method: Yb2O3, Pr6O 11, Sm2O3, Ce2O3, Gd2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials, weigh sodium hydroxide, sodium citrate and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, wherein the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1:1:0.6, and the ratio of alcohol to water is 1:1. After the reaction is completed, take out the sample, then wash and dry the sample with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 15h, the drying temperature is 50℃, and the drying time is 5h.
[0064] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: the high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 40:60, and the above two powders were mixed in a mass ratio of 1:5; then the mixed powder after roller milling was placed in an alumina crucible, kept at 850°C for 8 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 75°C to finally obtain Yb 0.2 Pr 0.2 Sm 0.2 Ce 0.2 G 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0065] Example 9
[0066] A high entropy ceramic oxygen adsorbent material, structural formula La 0.2 Sm 0.2 Pr 0.2 Ce 0.2 G 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0. 5O7, the preparation method thereof comprises the following steps:
[0067] (1) Preliminary treatment of oxygen adsorbent materials by hydrothermal method: La2O3, Sm2O3, Pr6O 11, Ce2O3, Gd2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials, weigh sodium hydroxide, polyvinyl alcohol and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, where the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1:1:0.6, and the ratio of alcohol to water is 1:1. After the reaction is completed, take out the sample, then wash and dry it with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 15h, the drying temperature is 50℃, and the drying time is 5h.
[0068] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: The high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 40:60, and the above two powders were mixed in a mass ratio of 1:5; then the mixed powder after roller milling was placed in an alumina crucible, kept at 850°C for 8 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 75°C to finally obtain La 0.2 Sm 0.2 Pr 0.2 Ce 0.2 G 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0069] Example 10
[0070] A high entropy ceramic oxygen adsorbent material, structural formula Yb 1 / 6 La 1 / 6 Pr 1 / 6 Sm 1 / 6 Ce 1 / 6 G 1 / 6BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7, the preparation method thereof comprises the following steps:
[0071] (1) Preliminary treatment of oxygen adsorbent materials by hydrothermal method: Yb2O3, La2O3, Pr6O 11, Sm2O3, Ce2O3, Gd2O3, BaCO3, Al2O3, Fe2O3, NiO and other raw materials, weigh sodium hydroxide, polyvinyl alcohol and other materials and dissolve them in a mixed solvent of alcohol and water, and then add the weighed powder into the reactor, where the mass ratio of raw materials, sodium hydroxide and sodium citrate is 1:1:1:0.6, and the ratio of alcohol to water is 1:1. After the reaction is completed, take out the sample, then wash and dry it with deionized water and alcohol, and preliminarily obtain the high entropy ceramic oxygen adsorbent material product; the reaction time is 150℃, the reaction time is 15h, the drying temperature is 50℃, and the drying time is 5h.
[0072] (2) Preparing porous high-entropy ceramic oxygen adsorbent material by mixed alkali method: the high-entropy ceramic oxygen adsorbent material product obtained by hydrothermal method was used as raw material, and NaCl and KCl were mixed in a mass ratio of 40:60, and the above two powders were mixed in a mass ratio of 1:5; then the mixed powder after roller milling was placed in an alumina crucible, kept at 850°C for 8 hours, and then washed several times with deionized water to wash away excess NaCl and KCl, and dried at 75°C to finally obtain Yb 1 / 6 La 1 / 6 Pr 1 / 6 Sm 1 / 6 Ce 1 / 6Gd 1 / 6 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7 nano powder high entropy ceramic oxygen adsorbent material.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high entropy ceramic oxygen adsorbent material, characterized in that: The structural formula of high entropy ceramic oxygen adsorbent material is: RBaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7, R-site elements are at least five of Yb, La, Pr, Sm, Ce and Gd.
2. The high entropy ceramic oxygen adsorbent material according to claim 1, characterized in that: The structural formula of the high entropy ceramic oxygen adsorbent material is: Yb 0.2 La 0.2 Pr 0.2 Sm 0.2 Ce 0.2 BaCo 2.5 Al 0.5 Fe 0.5 Ni 0.5 O7, high entropy ceramic oxygen adsorbent material has the shape of spherical powder, and the size of the powder is 50-500nm.
3. The method for preparing the high entropy ceramic oxygen adsorbent material according to claim 1 or 2, characterized in that: Here are the steps: (1) According to the structural formula of the high entropy ceramic oxygen adsorbent material, metal oxides of R-position elements, BaCO3, Al2O3, Fe2O3 and NiO are weighed according to the stoichiometric ratio; (2) dispersing and dissolving the powder, alkaline reagent and morphology control agent weighed in step (1) into a solvent, and then performing a hydrothermal reaction. After the reaction is completed, washing and drying are performed to obtain a porous high-entropy ceramic oxygen adsorbent material; (3) The high entropy ceramic oxygen adsorbent material and the chloride salt are mixed and ball-milled, and then the mixed powder is calcined to obtain the high entropy ceramic oxygen adsorbent material.
4. The method for preparing the high entropy ceramic oxygen adsorbent material according to claim 3, characterized in that: The metal oxide of the R-position element is Yb2O3, La2O3, Pr6O 11 , Sm2O3, Ce2O3 or Gd2O3.
5. The method for preparing the high entropy ceramic oxygen adsorbent material according to claim 4, characterized in that: In the step (2), the mass ratio of the powder, the alkaline reagent, the morphology control agent and the solvent is 1:(1-1.5):(1-1.5):(0.6-0.8), the alkaline reagent is sodium hydroxide; the morphology control agent is sodium citrate, sodium bicarbonate or polyvinyl alcohol.
6. The method for preparing the high entropy ceramic oxygen adsorbent material according to claim 5, characterized in that: The solvent includes alcohol and water in a mass ratio of 1: (1-1.5).
7. The method for preparing the high entropy ceramic oxygen adsorbent material according to any one of claims 3 to 6, characterized in that: The temperature of the hydrothermal reaction is 150-185° C. and the time is 5-15 hours.
8. The method for preparing the high entropy ceramic oxygen adsorbent material according to claim 7, characterized in that: The mass ratio of the high entropy ceramic oxygen adsorbent material to the chloride salt is 1:(5-10).
9. The method for preparing the high entropy ceramic oxygen adsorbent material according to claim 8, characterized in that: The chloride salt includes NaCl and KCl, and the mass ratio of NaCl to KCl is (40-55):(60-45).
10. The method for preparing the high entropy ceramic oxygen adsorbent material according to claim 3, characterized in that: The calcination temperature is 700-850°C and the calcination time is 8-10h.
Citation Information
Patent Citations
High-performance oxygen adsorbent and preparation method thereof
CN104857911A
Preparation method of Yb<1-x>M<x>BaCo<4>O<7> oxygen-enriched combustion absorbent material
CN106944023A
Rare earth zirconate high-entropy ceramic and preparation method thereof
CN116874298A
Ceramic material for making compact oxygen-permeable separation membrane and and its oxygen permeable membrane separator
CN1253849A
MANUFACTURING PROCESS FOR A SINTERED TRANSITIONAL METAL-HIGH-TROPY CERAMIC OXIDE COMPOSITE MATERIAL
DE102021110570A1